1999
DOI: 10.1002/(sici)1521-3862(199908)5:4<185::aid-cvde185>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Selective Metallization of Mg/NH3-Treated Teflon by Copper CVD

Abstract: The surface of Teflon, which can be made hydrophilic by a chemical treatment in a solution of solvated electrons in the presence of magnesium, can be restored by UV photochemical oxidation under oxygen. The Mg/NH 3 -treated Teflon surfaces are easily metallized in a single-step process by copper CVD when (VTMS)Cu(hfac) or (MHY)Cu(hfac) are used as precursors (where VTMS = vinyltrimethylsilane, hfac = hexafluoroacetylacetonate, and MHY = 2-methyl-1-hexene-3-yne). The growth rate of the copper film (thickness 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Laser-assisted CVD like conventional CVD relies on a volatile Cu precursor being delivered to the substrate in the gas phase. , Selective Cu deposition is achieved by heating the areas where Cu deposition is required with a laser, using the apparatus illustrated in Figure . This induces pyrolysis of the precursor and subsequent Cu film deposition .…”
Section: G Laser-assisted Mocvdmentioning
confidence: 99%
“…Laser-assisted CVD like conventional CVD relies on a volatile Cu precursor being delivered to the substrate in the gas phase. , Selective Cu deposition is achieved by heating the areas where Cu deposition is required with a laser, using the apparatus illustrated in Figure . This induces pyrolysis of the precursor and subsequent Cu film deposition .…”
Section: G Laser-assisted Mocvdmentioning
confidence: 99%
“…Surface modification has been achieved by low-energy ion beams; 2,3 argon plasma; 4 water-vapor plasma; 5 remote-hydrogen plasma; 6,7 oxygen plasma; 8 filament-assisted watervapor modification; 9,10 strong bases, such as KOH and LiOH; 11,12 solution-borne reducing agents, such as benzoin dianion/DMSO and NaBH 4 ; 13,14 and solvated electrons. 15,16 Further, a book and a review article discuss the surface modification of polymeric surfaces via plasmas. 17,18 However, it is the particular interest here to study how fluorocarbons interact with oxidizing plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Sazio et al [30] reported a deposition mechanism of metal or semiconductor around a central hole of diameter 1.0 µm that can be narrowed by a factor of 100 down to 25 nm or smaller. Moreover, the Teflon can be coated with copper using chemical vapour deposition [31] or metal-coated hollow waveguide technology [32]. Furthermore, the standard fabrication technology could produce a PCF with low roughness and little radiation losses.…”
Section: Resultsmentioning
confidence: 99%